PERSEPSI RESIDEN TENTANG PELAKSANAAN KONSELING KELOMPOK PADA PENYALAHGUNAAN NAPZA DI REHABILITAS RUMAH RAHAYU YAYASAN PLUS PONTIANAK - Nugraha, Prima; Purwanti, Purwanti; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe perception is a process for organizing and interpreting information and messages that are influenced by a number of psychological factors, including assumptions based on past experiences, moods and attitudes. Resident perception in this case refers to the implementation of group counseling which aims at the process of improvement, be it the behavior or positive attitude of the client towards a better, productive and recovery of drug dependence. The definition of drug abuse is the use of drugs and the like outside the purpose of treatment and science as well as medical indications and doctor's supervision for its own satisfaction which gives physical and psychological damage. So that there can be some appropriate adjustments so that group counseling gets an attractive appreciation by the residents. The problem in this study is